Understanding Psychological Safety in Health Care and Education Organizations: A Comparative Perspective. Issue 1 (2nd January 2016) - Edmondson, Amy C.; Higgins, Monica; Singer, Sara; Weiner, Jennie
Abstract : Psychological safety plays a vital role in helping people overcome barriers to learning and change in interpersonally challenging work environments. This article focuses on two such contexts—health care and education. The authors theorize differences in psychological safety based on work type, hierarchical status, and leadership effectiveness. Consistent with prior research, the authors employ cross-industry comparison to highlight distinctive features of different professions. The goal is to illuminate similarities and differences with implications for future psychological safety research. To do this, the authors review relevant literature and present analyses of large data samples in each industry to stimulate further research on psychological safety in both sectors, separately and together.